2011
DOI: 10.1148/radiol.11101466
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Petrosquamosal Sinus: High Incidence in Cases of Complete Aplasia of the Semicircular Canals

Abstract: The PSS presents a risk for cochlear implant surgery that can be detected by the neuroradiologist in advance. Venous CT angiography is advisable in certain cases. The previous assumption that a persistent PSS is encountered more frequently in cases of skull base deformity can be affirmed in the special situation of complete aplasia of the SCCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…However, several authors have reported it to be present in 11–89 % of CHARGE patients [9, 1315]. The highest incidence was described by Giesemann et al [14], in patients who all had aplasia of the SCCs. In our patient population, which included patients with partially and fully developed vestibular systems, a persistent petrosquamosal sinus was seen in 13 %.…”
Section: Discussionmentioning
confidence: 99%
“…However, several authors have reported it to be present in 11–89 % of CHARGE patients [9, 1315]. The highest incidence was described by Giesemann et al [14], in patients who all had aplasia of the SCCs. In our patient population, which included patients with partially and fully developed vestibular systems, a persistent petrosquamosal sinus was seen in 13 %.…”
Section: Discussionmentioning
confidence: 99%
“…Koesling et al did not analyze the PSS incidence in relation to RCOM and assessed only axial images. Giessmann et al described a high (up to 65%) incidence of PSS in cochlear implant candidates with complete aplasia of the semicircular canals, which was higher than that observed in association with other inner ear malformations [14]. The mean diameter of PSS observed in our study (1.1 mm, range 0.7–3.4 mm) was smaller than that observed by Giessmann et al (3.1 mm, range 1.0–4.4 mm) and San Millán Ruiz et al (2.6 mm, range 2.0–3.0 mm) [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Other consequences of emissary vein bleeds are epidural and subdural hematoma formations [6]. Venous anomalies of the internal jugular vein and sigmoid sinus are not uncommon in patients with otitis and labyrinthine dysplasia and may lead to enlargement of the emissary veins [7]. These patients are candidates for surgery and the description of these veins should be systematically included in temporal bone CT reports to provide awareness of the surgeon to avoid injuring these veins.…”
Section: A B Cmentioning
confidence: 99%